PERBANDINGAN PROKRASTINASI AKADEMIK MAHASISWA BERDASARKAN ANGKATAN - Dika Nurhasanah; Ilfiandra Ilfiandra (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
Procrastination refers to delaying the task of timely completion. Procrastination is a common behavior, especially in school settings and in student behavior. Academic procrastination is one of many types of delaying behavior that almost everyone shows from time to time. Academic procrastination is regarded as a domain-specific form of self-regulation failure. The purpose of this study is to describe the tendency of academic procrastination of students of Mechanical Engineering Education Department class of 2014, 2015, and 2016 with, gender and GPA. This study was conducted as a condition to obtain a Bachelor of Education degree. The research method used in this research is quantitative approach with descriptive research design. The instrument used in this study is to adopt the instrument developed by Solomon and Rothblum in 1984 called Procrastination Academic Scale Students (PASS). The results of research on mechanical engineering department students found that academic procrastination tendency is at the level of sometime procrastinator. The highest level of academic procrastination in the class of 2014, and no significant differences were found based on gender and GPA on student academic procrastination.